2022
DOI: 10.1136/bmjopen-2021-055381
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 seroprevalence in Pakistan: a cross-sectional study

Abstract: ObjectivesThis study adapted WHO’s ‘Unity Study’ protocol to estimate the population prevalence of antibodies to SARS CoV-2 and risk factors for developing SARS-CoV-2 infection.DesignThis population-based, age-stratified cross-sectional study was conducted at the level of households (HH).ParticipantsAll ages and genders were eligible for the study (exclusion criteria: contraindications to venipuncture- however, no such case was encountered). 4998 HH out of 6599 consented (1 individual per HH). The proportion o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 23 publications
2
11
0
Order By: Relevance
“…In the current study, a total of 11444 patients were enrolled finally and based on polymerase chain reaction (PCR), covid-19 was detected in 18.25% patients.In accordance with our study, a recent study carried out by Fazal Rahman et al reported 22.4% morbidity rate in their study 16 .A recent study carried out by Sarah Arif et al reported 6% prevalence of covid-19 which is not in accordance with our study 17 .Other studies also reported contrasting results as compared to our findings 18,19 . A recent study reported 19% morbidity rate which is almost similar to our findings 20 .…”
Section: Discussionsupporting
confidence: 66%
“…In the current study, a total of 11444 patients were enrolled finally and based on polymerase chain reaction (PCR), covid-19 was detected in 18.25% patients.In accordance with our study, a recent study carried out by Fazal Rahman et al reported 22.4% morbidity rate in their study 16 .A recent study carried out by Sarah Arif et al reported 6% prevalence of covid-19 which is not in accordance with our study 17 .Other studies also reported contrasting results as compared to our findings 18,19 . A recent study reported 19% morbidity rate which is almost similar to our findings 20 .…”
Section: Discussionsupporting
confidence: 66%
“… 29 Seroprevalence study in Pakistan during October to November 2020 although reported a lower seroprevalence of 7.1% based on a low sensitive rapid antibody testing (‘Bioperfectus’ kits for IgG/IgM), the estimated seroprevalence was 62 times higher than the reported number of cases before the survey period in the sampled districts. 30 High seroprevalence of SARS-CoV-2 IgG (39.2%) was reported from metropolis of the Brazilian Amazon from October 2020 to February 2021, which was also 10 times higher than the case reported by the health authority as of December 2020. 31 …”
Section: Discussionmentioning
confidence: 82%
“…29 Seroprevalence study in Pakistan during October to November 2020 although reported a lower seroprevalence of 7.1% based on a low sensitive rapid antibody testing ('Bioperfectus' kits for IgG/IgM), the estimated seroprevalence was 62 times higher than the reported number of cases before the survey period in the sampled districts. 30 High seroprevalence of SARS-CoV-2 IgG (39.2%) was reported from metropolis of the Brazilian Amazon from October 2020 to February 2021, which was also 10 times higher than the case reported by the health authority as of December 2020. 31 Although we found a higher seroprevalence (58.1%) in adults than children aged 1-17 years (38.6%), there was no difference in seroprevalence for older adults (aged 60 and above years) compared with middle-aged adults (aged 40-59 years), which supports the findings of the systematic review by Levin et al 32 No difference of seroprevalence between sexes was found through our study.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations